Coastal Lives, Nutritional Struggles: Anemia and Poor Diet Quality among Adolescent Girls in Indonesia - Ekawati, Dian Resky; Indriasari, Rahayu; Nurzakiah,; Hadju, Veni; Khuzaimah, Anna; Musfira, (International Journal of Child Health and Nutrition, 2026)
Objectives: Adolescent girls living in coastal areas are nutritionally vulnerable due to limited access to diverse and nutrient-rich foods. This study aimed to provide an overview of the nutritional profile and potential vulnerability to anemia among adolescent girls in this area. Methods: A descriptive cross-sectional study was conducted in January 2025 among 159 adolescent girls aged 11-18 years in the coastal area of Galesong Selatan, Takalar Regency, Indonesia. Data on hemoglobin levels and dietary intake were collected using Hemocue 301 and two non-consecutive 24-hour recalls. Diet quality was assessed using the Diet Quality Index for Adolescents (DQI-A) adapted to Indonesian guidelines, and all data were analyzed descriptively. Results: The prevalence of anemia among adolescent girls was 42.8%, with 23.9% classified as mild and 18.9% as moderate anemia. The median DQI-A score was 40.33, with subcomponent scores of DQ: 5.95, DD: 71.43, and DE: 40.14, indicating overall poor diet quality. Most participants had moderate dietary diversity (60.4%) and low dietary equilibrium, with 73.0% consuming less than half of the recommended daily nutrient intake (<50% RDA). The average intake of energy, protein, iron, folate, and vitamin C was markedly below the RDA, showing substantial nutrient inadequacy. Although weekend intake was slightly higher, nutrient levels remained insufficient to meet daily requirements. Conclusions: Improving adolescent diet quality through balanced, micronutrient-rich food intake and adherence to iron-folic acid supplementation is essential not only to prevent anemia but also to strengthen vascular health and reduce future risks of congenital vascular anomalies. The findings can inform school-based nutrition education, local food optimization, and policy planning to support adolescent health in coastal communities.